2021
DOI: 10.52970/grhrm.v1i2.54
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Work Motivation and Work Environment in Improving Job Satisfaction

Abstract: This study aims is to analyze the effect of work motivation on the satisfaction of management lecturers and analyze the effect of the work environment on the satisfaction of management lecturers at a private university in the city of Makassar. This type of research is explanatory research. The sample of this research is management lecturers at private universities in Makassar city, Data use purposive random sampling total 105 respondent. The research period was carried out in February 2020-May 2020. The method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 31 publications
4
28
1
8
Order By: Relevance
“…However, this present study suggests that intrinsic rewards, classroom environment, and CCT significantly impacted the lecturer’s job satisfaction. The current study sought agreement with the work by Basalamah and As’ad (2021) that the classroom facilitated the delivery of teaching instruction while the academic felt empowered and satisfied. However, the study’s results emphasized that the classroom environment was insignificantly related to the lecturer’s job performance.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, this present study suggests that intrinsic rewards, classroom environment, and CCT significantly impacted the lecturer’s job satisfaction. The current study sought agreement with the work by Basalamah and As’ad (2021) that the classroom facilitated the delivery of teaching instruction while the academic felt empowered and satisfied. However, the study’s results emphasized that the classroom environment was insignificantly related to the lecturer’s job performance.…”
Section: Discussionmentioning
confidence: 83%
“…Correspondingly, Pham-Thai et al (2018) highlighted an increase in employee productivity upon the increase in the pay structure. The recent empirical work demonstrated that FRs positively influence job performance, while the employees are more concerned about the extrinsic reward systems that include salary, bonuses, or commissions that could increase their satisfaction and the organization profits ( French et al, 2020 ; Basalamah and As’ad, 2021 ). Accordingly, the following hypotheses are suggested:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employee motivation may be achieved through a variety of variables that assist worker motivation, and motivation will invariably affect employee productivity, which will drive corporate performance. Both business managers and recruiters have been involved in the game of workplace motivation, where financial compensation is the most significant motivating factor for professionals to enhance their organizational productivity in workplace; some other set of factors includes management connection, practice environment, employee's willingness, stability, equality, chance for career progress, and reasonable continuous assessment (Basalamah & Ajmal, 2021). These motivational aspects will boost staff morale and increase performance.…”
Section: Employees' Motivational Factorsmentioning
confidence: 99%
“…Earning, advancement, avoidance of punishments and criticism, and the environment of understanding within the team are all key aspects in professional competence. Work motivation may be classified into three types (Basalamah and As'ad, 2021): 1) Internal motivation-the mood among the team, the direct manager consultation. (Dahlin, Chuang and Roulet, 2017); 2) Good external motivation like self-esteem, wages, and opportunity (Martinez and Hurtado, 2018) for advancement in career; 3) Negative external motivationlike avoiding unconstructive criticism (Graham, 2020), avoiding the possibility of losing the job.…”
Section: Benefits Offered By Using Teambuildingmentioning
confidence: 99%